Reduction of Air Condition Energy Consumption by Redundant Energy Gains Modification - Masiukiewicz, Maciej; Szmolke, Norbert; Gużda, Arkadiusz; Somogyi, Viola; McNamara, Greg (Instal, 2023)
For a selected building in a specific location and conditions encountered, heat gains from sun exposure, resident people, equipment, lighting, and window partitions were calculated depending on the time of day (hourly for a year), the number, and the activity of people in the building. The heat and humidity balance was performed. This allowed the cooling and heating demand to be determined. The air conditioning system was adjusted to the demand. The operation of the system was simulated by showing the loads (hourly for a year). The load flexibility of the air conditioners was presented. Heat gains have been determined and ranked according to which has the greatest influence on the air conditioning load. Solutions were proposed to reduce the heat load in the building. As a result of the research, methods were presented for reducing the energy consumption of air conditioning by modifying the factors causing redundant energy gains.